Effects of compost-derived humic acid on the bio-dechlorination of pentachlorophenol in high iron content paddy soil - Yu Xiao (Elsevier, 2021)
Pentachlorophenol (PCP) is a common residual organic pollutant in paddy soil, and its harmful effects on soil ecosystems have been confirmed. Humic acid (HA) could act as an electron shuttle to promote the reductive dechlorination of PCP under anaerobic conditions. Humic-like substances produced by composting of kitchen waste were able to facilitate the reductive dechlorination of PCP during Fe(III) oxide reduction by iron-reducing bacteria. However, the effects of compost-derived HAs on reductive dechlorination of PCP in a paddy soil system with a high iron content have not been fully confirmed. The characteristics of HAs from different stages of composting during bio-dechlorination of PCP were still unclear. The functional components of compost-derived HAs, which are responsible for reductive dechlorination of PCP in different stages of composting, also need further investigation. In this study, we conducted a series of experiments on the Guangdong paddy soil system with high iron content (17.5 mg kg−1) to investigate the reductive dechlorination of PCP by HA in the early, middle, and later stages of food waste composting. The results showed that the middle- and late-stages of compost-derived HAs all promoted reductive dechlorination of PCP in the paddy system, but it was opposite in the early-stage. Significant differences were also presented in the components of HAs from different stages of composting. The early-stage compost-derived HAs contain numerous easy degradable components, it would inhibit the dechlorination of PCP by the changes of microbial metabolism in paddy soil. Compost-derived HAs in the middle composting stage showed the best reductive dechlorination effects on PCP. The reason might be that the compost-derived HAs in the middle composting stage could act both as electron donors and transfers. The electron transfer capacities (ETC) of middle-stage compost-derived HAs were significantly higher than those in the early and later composting stages. Compared with the natural HAs in the soil system, compost-derived HAs contained more chlorinated products with lower toxicities after the PCP degradation. This result mainly contributed to the detoxification and mineralization of PCP in the soil. These findings clarified the effects of compost-derived HAs on PCP bio-dechlorination in paddy soil with high iron content, identifying the optimal phase of compost-derived HA and providing a theoretical basis for the utilization of kitchen waste composting as a resource of HA.